(untitled) (Research, Society and Development, 2026)
Introduction: Bees are an essential part of wildlife. However, deforestation, human-caused wildfires, and increasingly frequent agricultural and human activities in forested areas contribute to the occurrence of incidents involving Africanized bees. Aim: This study aimed to describe the epidemiological profile of bee attacks between January 2010 and December 2022, incorporating the pandemic period as an axis of analysis. Methods: Data on incidents involving bees were obtained of the the Health Information System of the Brazilian Ministry of Health from the July to December 2023. Results: The results demonstrated a progressive increase in the number of bee-related incidents during the evaluated period and the impact of measures adopted during the Covid-19 pandemic on the number of bee venom intoxications in Brazil, which decreased during the pandemic years; the seasonality of cases and the distribution of cases by victims’ sex; the distribution by age group and the number of cases and deaths, which are higher in the states of Tocantins, Roraima, and Rio Grande do Norte and Roraima and Tocantins, respectively. Conclusions: Despite the pandemic, the data show that incidents involving bees continue to increase steadily, and public policymakers would benefit from implementing measures aimed at improving environmental and health education to reduce the number of bee attacks.